The Poetics of Historical Perspectivism Breitinger's Critische Dichtkunst and the Neoclassic Tradition - Anne Kowalik, Jill (UNC Studies in the Germanic Languages and Literatures, 1992)
Jill Kowalik reevaluates J. J. Breitinger's "Critische Dichtkunst" (1740) with regard to a heretofore neglected aspect of aesthetics in the early eighteenth century, namely how poesis and historiography could increasingly come to resemble each other in their assumptions, purposes, and methods of representation. The central argument states that historians of this period began to utilize the concept of historical perspectivism only after its development as an interpretive tool by the aesthetic thinkers of the early Enlightenment. The "Critische Dichtkunst" is examined in terms of three disparate traditions: the modern reception of Aristotle's "Poetics", Horace's "Ars poetica", and the Quarrel between the Ancients and the Moderns the model of consciousness proposed by Leibniz that describes the mind as a ceaseless process of historical intellective integration and the German reception of French neoclassical authors, especially Dubos, whose notion of historical probability was radicalized by Breitinger and later appropriated by poets and historians alike.